Implicações intermidiáticas em A arte de produzir efeito sem causa e O grifo de abdera de Lourenço Mutarelli - Erthal, Claudia (2023)
This work seeks to analyze the hybridized and intermedial contributions and the combination of media in A arte de produzir efeito sem causa and O grifo de Abdera, by Lourenço Mutarelli. The analysis also reveals the use of resources such as intertextuality, self-referentiality, (self)parody and (self)irony in the novels. The second novel is metafictional, presenting more than one narrative planes, which occurs through the combination of novel and graphic novel. The theoretical reference of this discussion is based on Todorov (1980) and Bakhtin (2014) regarding the capacity of the novel to absorb other genres, extending to the notions of hybridism on contemporary literature, observed from modern literature, according to Candido (1989), Pellegrini (2003), Perrone-Moises (2016) and Resende (2008). Methodologically, the investigation is interdisciplinary, bibliographical and comparative, relying on intermedia theoretical and analytical models, presented by Rajewsky (2012) and Elleström (2017), as well as the approach of the articulation of image and written texts proposed by Santaella (2012). The analysis is also linked to the dialectical and sociological perspective, considering the necessary articulations of the textswith the extraliterary context.